Psychological readiness of a music therapist to work in special education - Shulzhenko, Oleksandr (Professional Art Education, 2024)
The article presents the results of theoretical and methodological analysis of scientific achievements of world and domestic scientists of the study of the problem of psychological readiness of specialists who study it in the dimension of special education and correctional and rehabilitation impact on children with violations of intellectual, autistic, speech and kinesthetic dysontogenesis. Analysis of literary sources showed that the psychological readiness of a specialist of special education is an integral education of the teacher consisting in the motivational, emotional and activity attitude of the adult to change in behavioral, regulatory, developmental, intellectual, sensual perception of cooperation with the child aimed at correcting and compensation for central nuclear disorders and their consequences.Methods & methodology. The psychological readiness of the music therapist is presented as the following components: praxeological, assertive and internal. Each component is represented by parameters of intellectual, motivational, volitional, self-regulatory, evaluation, creative, creative, communicative, correctional-compensatory psychological mechanisms.The scientific novelty consists in the author's definition of criteria and levels of psychological readiness of a specialist in musical development for adequate interaction with children differentiated by one or another nosology.Results. It is determined that the personal traits of a musician-teacher are manifested in a situation of his awareness of the need for special professional training to perceive the psychological characteristics of children with special educational needs. It is noted that without the formed psychological readiness of a specialist of musical direction, his supervision of training, psychological support, a negative attitude towards special children and cooperation with them is laid. Music therapy requires special training of specialists who are not only competent in the field of music, the influence of music, the use of musical instruments, but what ensures the phenomenon of its effectiveness and reliability of scientific and practical results. Music therapy has recently begun to be used in special education and this work included specialists in the musical direction of activity. Scientists studying the pedagogical and psychological qualities of a music teacher point to criteria such as high-quality musical abilities, the ability to encourage children to cooperate, to show musical abilities in these children, develop musical taste in them, understanding of the material, make efforts while learning to play instruments, creatively approach the use of musical material and systematically support motivation and contribute to the creative development of children. The article presents levels of professional awareness by music therapists of the problems of cooperation with children of the above difficulties, acceptance, assimilation, processing and implementation of musical content. It is determined that such cooperation should take place in the context of not only musical but also special work within the framework of musical psychotherapy.Conclusions. It is concluded that it is necessary to develop and test a structural and functional model of professional special psychological training of music specialists with a significant emphasis on psychotherapeutic assistance.
Keywords: music therapy; special education; psychological readiness; music therapist; children with special educational needs